Absent X‐linked inhibitor of apoptosis protein expression in T cell blasts and causal mutations including non‐coding deletion. Issue 1 (10th February 2022) - Abdrabou, Shimaa Said Mohamed Ali; Toita, Nariaki; Ichihara, Shin; Tozawa, Yusuke; Takahashi, Michiko; Fujiwara, Shin‐ichi; Ashida, Toshifumi; Ohara, Osamu; Ariga, Tadashi; Manabe, Atsushi; Konno, Mutsuko; Yamada, Masafumi
Abstract: Background: X‐linked inhibitor of apoptosis protein (XIAP) deficiency is one of inborn errors of immunity characterized by recurrent hemophagocytic lymphohistiocytosis and refractory inflammatory bowel disease (IBD), mimicking Crohn's disease. The aim of this study is to make an accurate diagnosis of XIAP deficiency based on genetic and XIAP expression studies and to investigate endoscopic findings shared by patients with this disease. Methods: Four male patients with recurrent hemophagocytic lymphohistiocytosis and long‐term refractory IBD were studied for the diagnosis of XIAP deficiency. Endoscopic findings of the four patients were also studied in parallel. Results: These four patients were diagnosed with XIAP deficiency based on the absent XIAP expression in cultured T‐cell blasts. Sequence analysis of the responsible gene, XIAP, demonstrated two novel nonsense mutations of p.Gln114X and p.Glu25X, and a previously reported nonsense mutation of p.Arg381X. Although no mutations in the coding region were detected in the fourth patient, further studies demonstrated a novel 2, 199 bp deletion encompassing non‐coding exon 1, presumably affecting transcription and stability of XIAP mRNA. All of the patients eventually underwent hematopoietic stem cell transplantation, leading to a complete or partial remission of IBD. These four patients shared an endoscopic finding of multiple wide and longitudinal ulcers with straight and non‐raised edge in the colon. Conclusions: X‐linked inhibitor of apoptosis protein expression in T‐cell blasts could facilitate the diagnosis of this disease, especially with causal mutations in non‐coding regions.